2021
DOI: 10.3389/fphar.2021.726707
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Exerts Anti-inflammatory and Mucus Barrier Protective Effects by Enriching Akkermansia muciniphila in Mice With Ulcerative Colitis

Abstract: The present study aimed to determine if metformin exerts anti-inflammatory and mucus-protective effects via the gut microbiota. Metformin has extensive benefits including anti-inflammatory effects. Previous studies showed that metformin changed the gut microbiota composition and increases the number of goblet cells. Intestinal dysbiosis and goblet cell depletion are important features of ulcerative colitis (UC). The underlying mechanism and whether metformin can improve the mucus barrier in UC remain unclear. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 80 publications
0
33
0
Order By: Relevance
“…However, we confirmed that metformin did not directly affect goblet cell maturation under radiation exposure. Others have reported that metformin alleviated DSS-induced colitis by increasing the levels of potential probiotics (e.g., Akkermansia muciniphila ) [ 38 ] and attenuated aging-related leaky gut by modulating the microbiome–goblet cell–mucin axis [ 36 ]. Therefore, metformin-induced goblet cell maturation in a mouse model may be related to microbiome alterations in the irradiated intestine.…”
Section: Discussionmentioning
confidence: 99%
“…However, we confirmed that metformin did not directly affect goblet cell maturation under radiation exposure. Others have reported that metformin alleviated DSS-induced colitis by increasing the levels of potential probiotics (e.g., Akkermansia muciniphila ) [ 38 ] and attenuated aging-related leaky gut by modulating the microbiome–goblet cell–mucin axis [ 36 ]. Therefore, metformin-induced goblet cell maturation in a mouse model may be related to microbiome alterations in the irradiated intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Several strategies to modulate gut microbiota currently exist and more are being developed. Fecal microbiota transplantation, [ 4 ] medication, [ 5 , 6 ] or whole‐diet modification [ 7 , 8 ] can all lead to significant changes in gut microbiota composition. However, implementing these strategies may be challenging or have adverse effects of their own.…”
Section: Introductionmentioning
confidence: 99%
“…Ke et al have found that metformin restored intestinal barrier function by increasing the expression of mucin 2 in mice with ulcerative colitis induced by dextran sulfate sodium (DSS). 30 Myosin light-chain kinase (MLCK) is an enzyme activating the myosin light chain (MLC) and participating in cytoskeleton contraction and TJ regulation. Zhu et al have demonstrated that metformin stabilizes TJ proteins and improves intestinal barrier function by inhibiting the MLCK-MLC signaling pathway in Caco-2 cell monolayers.…”
Section: Introductionmentioning
confidence: 99%